The transfer of patients and its ergonomic aspects: a study conducted at a university hospital lifting center - Rossi, Cristiane Gonzales; Rocha, Renata Marchetti; Alexandre, Neusa Maria Costa (Revista da Escola de Enfermagem da USP, 2001)
The purpose of this study was to evaluate ergonomic aspects involved in using a stretcher and a wheel chair to transfer patients. 249 transfers carried out by the workers of a university hospital lifting sector were observed. The observations showed that the idea of having a team to transfer patients has to be stimulated but the members of the team require specific training in handling and transferring patients. Mechanical equipment and other devices should also be available.